Spatial Coordination of Kindlin-2 with Talin Head Domain in Interaction with Integrin β Cytoplasmic Tails - Bledzka, Kamila (American Society for Biochemistry and Molecular Biology, 2012)
Both talin head domain and kindlin-2 interact with integrin β cytoplasmic tails, and they function in concert to induce integrin activation. Binding of talin head domain to β cytoplasmic tails has been characterized extensively, but information on the interaction of kindin-2 with this integrin segment is limited. In this study, we systematically examine the interactions of kindlin-2 with integrin β tails. Kindlin-2 interacted well with β(1) and β(3) tails but poorly with the β(2) cytoplasmic tail. This binding selectivity was determined by the non-conserved residues, primarily the three amino acids at the extreme C terminus of the β(3) tail, and the sequence in β(2) was non-permissive. The region at the C termini of integrin β(1) and β(3) tails recognized by kindlin-2 was a binding core of 12 amino acids. Kindlin-2 and talin head do not interact with one another but can bind simultaneously to the integrin β(3) tail without enhancing or inhibiting the interaction of the other binding partner. Kindlin-2 itself failed to directly unclasp integrin α/β tail complex, indicating that kindlin-2 must cooperate with talin to support the integrin activation mechanism.